Evaluation of Shampakadi Basti and Kshar Basti along with Pristha Basti in Trik Grah (Ankylosing Spondylitis) (International Journal of Ayurveda and Pharma Research, 2024)
Basti is considered the most effective treatment for Vata, as well as for Pitta, Kapha, and Rakta (blood) in Samsarga, and Sannipata Doshaas. Within the 'Nanatmaja vyadhi' of Vata, Charaka sutra 20/10 mentions a total of eighty types of Vata Rogas, known as Ashiti Roga. Trik-Asthi is sacrum bone. Sacroiliitis is often the earliest manifestation of ankylosing spondylitis. Ankylosing spondylitis is a complex, and systemic inflammatory rheumatic disease mainly affecting the axial skeleton, with the potential to cause severe debilitation. Fibrosis and ossification of tendon, ligament and capsule insertion at the area of sacroiliac and intervertebral discs are the main characteristics of ankylosing spondylitis. Eighty types of Nanatmaja Vata Vikara caused by Vata. Trik Grah one of the Vata Nanatamaja Vyadhi. Vata-Vyadhies can be considered as a group of such diseases, which Modern Science has given different names. Methods: This clinical study was done to “Evaluation of Shampakadi Basti and Kshar Basti along with Pristha Basti in Trik Grah (ankylosing spondylitis)”. Basti Karma is known to be the best for Vata disorders thus for this research, open labelled clinical study was done wherein 50 patients were taken in random manner having symptoms of Trik Grah and were divided into two groups, Group A received Shampakadi Basti along with Pristha Basti and Group B received Kshar Basti along with Pristha Basti daily for 8 days. Results: Evaluation and the result of both the group exhibited that the improvement provided by group B was better in both sign & symptoms like Sandhi Shool (pain), Sandhi Jadyata (stiffness), Angamarda (fatigue), quality of sleep in comparison to group A. Conclusion: As Vata vitiation is a cause Trik Grah, no other treatment modality act as good as Basti. As Ama involvement was there, which was obstructing or vitiating the Samanya Vata action, thus Shampakadi Basti and Kshar Basti along with Pristha Basti showed encouraging results in this disease.